PELATIHAN PEMBUATAN VIDEO PRODUK UNTUK MEDIA SOSIAL UMKM DI EMBUNG TIRTA KENCANA - Purba, Florensa Rosani; Felicia Ruth Andini Susilo; Jeremiah Jacob Hartadhi; Marco Junaedi; Arnoldina Yansensia Ose Murtiningrum (Servirisma, 2024)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in Indonesia's economy, yet many MSME actors often face challenges in leveraging digital technology as a marketing tool. Social media platforms like Instagram, TikTok, and Facebook provide significant opportunities to expand markets through engaging visual content. This community service program aims to enhance the ability of MSMEs in Embung Tirta Kencana to utilize social media through training in promotional video creation. The program focuses on digital marketing strategies, visual content creation techniques, and the use of editing software such as CapCut, Kinemaster, and VivaVideo. The training methods include theoretical and practical sessions, where participants utilize their own products as promotional materials. The results reveal that although participation in the training remains low, some participants have begun utilizing social media for promotion. However, challenges such as limited technical knowledge and motivation still hinder optimal implementation. Therefore, continued training and ongoing support are necessary for MSMEs to maximize the potential of social media in enhancing their competitiveness and boosting product sales.